Design of non-motorized mobility plan for warm climate cities case: Hermosillo, Sonora, Mexico - Moreno Freydig, Hugo César (Premio Internacional de tesis de investigación 2017. Transformación urbana. Densidad habitacional y ciudad compacta, 2016)
This research seeks to generate exploration of infrastructure elements needed to promote a proper integration of sustainable urban mobility in cities with arid or hot-dry climate, using the case of Hermosillo, Sonora, Mexico; focusing on non-motorized transport (walking and cycling, as well as promoting public transportation). This is made by analyzing the downtown area of the case study city. The approach to this is in response to an increased use of private vehicles, which may cause economic, social and environmental problematics. To do this it was studied the general recommendations of Transit Oriented Development. TOD is an urban model design and planning around public transport that works as a strategy to give solutions to local and regional mobility, minimizing the reliance on automobiles. Due to the specific necessities of cities with warm climate, the research uses TOD as a baseline to generate a specific set of design principles that are specially made for arid urban environments, looking to promote a proper way to walk, cycle and use public transportation systems, despite the presence of high temperatures and other climate difficulties that can affect the performance of people in public spaces. As a result of the analysis, design schemes were presented to apply in the area, which were set into context according to the actual information and characteristics of the study area, presenting a series of images that illustrate the proposal in its contextualized urban environment.